Superamphiphilic Silicon Wafer Surfaces and Applications for Uniform Polymer Film Fabrication. Issue 21 (29th March 2017) - Zhu, Zhongpeng; Tian, Ye; Chen, Yupeng; Gu, Zhen; Wang, Shutao; Jiang, Lei
Abstract: Silicon wafers have been widely used in the semiconductor industry for many decades. Over the past decades, with the development of organic optoelectronic materials, silicon‐based organic–inorganic hybrid devices have received more and more interest in fundamental and applied research. To obtain uniform organic films for hybrid devices, superamphiphilic surfaces, on which both water and oil can spread completely, show great advantages. Herein, we prepared superamphiphilic silicon wafer surfaces with contact angles (CAs) near 0° for both water and typical organic liquids. Interestingly, lateral force mode (LFM) atomic force microscopy (AFM) images indicate that the superamphiphilicity is induced by alternating hydrophilic and hydrophobic nanodomains. By making use of these superamphiphilic silicon wafer surfaces, uniform polypyrrole (PPy) films were generated in both water and cyclopentanone, providing a versatile and effective way for the integration of organic optoelectronic materials with inorganic microelectronic devices. Abstract : Alternating nanodomains : Superamphiphilic silicon wafer surfaces with alternating hydrophilic and hydrophobic nanodomains were generated by a three‐step process. A mechanism to explain the spreading behavior of both water and oil on these superamphiphilic silicon wafer surfaces was proposed, and it was shown that uniform polypyrrole films can be generated on such surfaces.